Patterns of drug use in jails in Peru - Colque Casas, José Luis (2018)
The objective of this study was to determine patterns of drug use in subjects held in a penitentiary in Lima. It is a descriptive cross-sectional study and the sample consisted of 330 male inmates, from whom the information of 279 inmates could be validated. The age among the inmates varied from 18 to over 65 years, being the age of highest prevalence (31.2%) between 31 to 40 years, the intern with younger age is 18 years and the oldest age was 75 years. A questionnaire of multiple options was used, adapted for the present investigation, which is divided into five areas: a) educational level, b) civil status, c) legal situation, d) crime and e) drug consumption. Likewise, the Drug Use Questionnaire (DAST-20) was used, whose reliability varies between 0.92 to 0.94. The Alcohol Disorders Identification Questionnaire (AUDIT) was also used, whose level of reliability was above 0.90. Among the most important conclusions, the most prevalent drugs among the inmates are alcohol, tobacco, marijuana, cocaine hydrochloride and basic cocaine paste, these being the ones with the highest consumption in the last 30 days. Age, level of education and crime significantly influence drug use inside the penitentiary.